Perancangan Sistem Pendukung Keputusan Seleksi Penerimaan Karyawan Dengan Metode Simple Additive Weighting (SAW) (Studi Kasus Toko Markas Hobby) - Dadi Rosadi; Siti Khotijah (STMIK Mardira Indonesia, Bandung, 2017)
Selection process for new employees at the Markas Hobby is still done manually, the application file new candidates will be evaluated by comparing the file contents with the specified criteria. Selection of the files that meet the criteria then continued with the interview process. The series of processes followed by a series written the tests, including psychological tests, tests of academic potential and so on. Statements this thesis aims to build a Decision Support System Selection Recruitment of new uses Simple Additive weighting method (SAW). This method was chosen because it can determine the weight values for each attribute, and then proceed with the ranking process that will select the best alternative from several alternatives, In this case, the alternative is entitled to be accepted as a new employee in accordance with criteria specified. In developing this application writer use the method of RUP (Rational Unified Process), with Descriptive Research Methodology and Action Research Methodology. While the system implementation using PHP programming language and MySQL as the database. The decision support system may help section Recruitment in making decisions for the recruitment process at Markas Hobby more easily and quickly. Keywords: decision support system, simple additive weighting method (SAW)